Brentuximab vedotin for paediatric relapsed or refractory Hodgkin's lymphoma and anaplastic large-cell lymphoma: a multicentre, open-label, phase 1/2 study. Issue 10 (October 2018) - Locatelli, Franco; Mauz-Koerholz, Christine; Neville, Kathleen; Llort, Anna; Beishuizen, Auke; Daw, Stephen; Pillon, Marta; Aladjidi, Nathalie; Klingebiel, Thomas; Landman-Parker, Judith; Medina-Sanson, Aurora; August, Keith; et al.
Summary: Background: Despite remarkable progress in the treatment of newly-diagnosed classical Hodgkin's lymphoma and systemic anaplastic large-cell lymphoma, treatment of relapsed or refractory disease remains challenging. The aims of this study were to assess the safety, tolerability, recommended phase 2 dose, and efficacy of brentuximab vedotin in paediatric patients with relapsed or refractory Hodgkin's lymphoma or systemic anaplastic large-cell lymphoma. Methods: This open-label, dose-escalation phase 1/2 study was done at 12 centres across eight countries (France, Germany, Italy, Mexico, The Netherlands, Spain, UK, and USA). We recruited paediatric patients aged 7–18 years with relapsed or refractory classical Hodgkin's lymphoma or systemic anaplastic large-cell lymphoma, for whom standard treatment was unavailable or no longer effective. Participants were allocated to receive brentuximab vedotin at 1·4 mg/kg (phase 1) or 1·8 mg/kg (phases 1 and 2) via intravenous infusion once every 3 weeks for up to 16 cycles. Dose escalation was done via a 3+3 design. Key exclusion criteria were stem-cell transplantation less than 3 months before administration of the first dose of study drug, presence of cytomegalovirus infection after allogeneic stem-cell transplantation, previous treatment with an anti-CD30 antibody, and concurrent immunosuppressive or systemic therapy for chronic graft-versus-host disease. Primary outcomes were safety profile in the safety-evaluable population and maximum tolerated dose, recommended phase 2 dose, pharmacokinetics (phase 1), and proportion of patients who achieved best overall response (phase 2; evaluated by an independent review facility) in the response-evaluable population. This trial is registered withClinicalTrials.gov, numberNCT01492088 . Findings: Between April 16, 2012, and April 4, 2016, we screened 41 paediatric patients and enrolled 36 (aged 7–18 years), of whom 19 had relapsed or refractory classical Hodgkin's lymphoma and 17 had relapsed or refractory systemic anaplastic large-cell lymphoma. At the data cutoff (Oct 12, 2016), all 36 patients had discontinued study drug treatment; the most common reason was progressive disease (15 patients). The maximum tolerated dose was not reached. The recommended phase 2 dose was 1·8 mg/kg. The proportion of patients who achieved overall response was 47% (95% CI 21–73) for classical Hodgkin's lymphoma and 53% (28–77) for systemic anaplastic large-cell lymphoma. All 36 patients had a treatment-emergent adverse event and 16 patients (44%) had at least one grade 3 or worse treatment-emergent adverse event. The most common treatment-emergent adverse events were pyrexia (16 [44%] of 36) and nausea (13 [36%]). The most common grade 3 or worse treatment-emergent adverse events were neutropenia (four [11%]), increased γ-glutamyl transpeptidase (two [6%]), and pyrexia (two [6%]). 12 (33%) patients had transient, limited-severity peripheral neuropathy. Eight patients (22%) had a serious adverse event; three (8%) had a drug-related serious adverse event. One patient died of cardiac arrest (disease progression of a large huge mediastinal mass, unrelated to the study drug). Paediatric pharmacokinetic profiles were consistent with those from studies of adult patients. Interpretation: Brentuximab vedotin has manageable toxicity and is associated with clinically meaningful responses in paediatric patients with relapsed or refractory Hodgkin's lymphoma or systemic anaplastic large-cell lymphoma, and could allow subsequent stem-cell transplantation in some patients who were initially ineligible for stem-cell transplantation. Funding: Millennium Pharmaceuticals Inc.